Centrifugal Test and Instability Model Analysis of Excavation Surface Stability of a Shield Tunnel in a Clay Layer - Niu, Haoshuang; Weng, Xiaolin; Hu, Jibo; Hou, Lele (Frontiers in Earth Science, 2022)
In order to study the variation law of support force and instability failure mode of excavation face under different soil parameters, a complete set of centrifugal model seepage test device is independently developed. Through centrifugal tests with different C / D, internal friction angle and different water head height, the results show that with the increase of the retreating displacement S of the excavation surface, the support force P of the excavation surface can be divided into three stages: rapid decline (S < 1.5D%), slow rebound after reaching the limit support force Plim (1.5D% ≤ S ≤ 3D%), and gradually reaching the stable value (3D% < S); With the increase of C / D, the ultimate support pressure on the excavation face gradually increases and tends to be stable. For different soil properties, when C / D > 1.5, the ultimate support pressure on the excavation face tends to be stable; With the increase of internal friction angle, the ultimate support pressure decreases gradually, and when φ＞ After 40 °, its influence on support pressure can be ignored; With the increase of head height Hw, the ultimate support pressure increases linearly. By establishing a numerical analysis model and analyzing the instability modes of soil under different C / D, internal friction angle and cohesion, it can be obtained that the instability mode of soil in front of the excavation face has a great correlation with soil C / D and internal friction angle, and the influence of cohesion is minimal. With the increase of C / D, the soil changes from overall failure to local failure, The change of C / D mainly affects the height of soil arching effect and the width of the wedge below, while the internal friction angle mainly affects the width of the wedge and the instability angle of soil.